Adverse childhood experiences among youth reported to child welfare: Results from the national survey of child & adolescent wellbeing. (August 2017) - Garcia, Antonio R.; Gupta, Meera; Greeson, Johanna K.P.; Thompson, Allison; DeNard, Christina
Abstract: The negative influence of adverse childhood experiences (ACEs) on social, emotional, and behavioral (SEB) outcomes are well documented. However, no research to date has examined the effect of ACEs on SEB outcomes in youth who received mental health services after reporting to the child welfare system. This study's analyses of data from the National Survey of Child and Adolescent Well-Being II revealed that the most prevalent ACEs included hospitalization for a medical condition, neglect, and exposures to domestic and community violence. Logistic regression of this data showed that the odds of being diagnosed with internalizing problems increased with age and when sexual abuse was reported. The results also showed that compared to Caucasian youth, Latinos were less likely to be diagnosed with externalizing behaviors, even when sexual abuse had been reported. Contrary to one of this study's hypotheses, mental health service use within the past 18 months increased the odds of being diagnosed with SEB problems. These findings highlight the persistence of SEB problems despite receipt of mental health services. Future research should assess the impact of interventions that aim to mitigate poor SEB outcomes due to ACEs, especially sexual abuse.